2009
DOI: 10.1007/s11123-009-0140-z
|View full text |Cite
|
Sign up to set email alerts
|

Price cap regulation and the ratchet effect: a generalized index approach

Abstract: Regulation, Technical change, Price cap, Ratchet effect, Incentives, D21, D24, L51, L95,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The cases of England and Wales are paradigmatic, and several studies have assessed changes in the productivity of English and Welsh water companies (e.g. Saal et al, 2007;Bottaso and Conti, 2009;Portela et al, 2011;Maziotis et al, 2014). Because of the advantages of benchmarking, studies on the efficiency and growth in the productivity of water utilities have also been carried out in other countries, such as Portugal (Carvalho et al, 2012), Australia (Worthington, 2014), Spain (Sala-Garrido et al, 2012), Italy (Guerrini et al, 2013), and France (Lannier and Porcher, 2014), among others.…”
Section: Introductionmentioning
confidence: 99%
“…The cases of England and Wales are paradigmatic, and several studies have assessed changes in the productivity of English and Welsh water companies (e.g. Saal et al, 2007;Bottaso and Conti, 2009;Portela et al, 2011;Maziotis et al, 2014). Because of the advantages of benchmarking, studies on the efficiency and growth in the productivity of water utilities have also been carried out in other countries, such as Portugal (Carvalho et al, 2012), Australia (Worthington, 2014), Spain (Sala-Garrido et al, 2012), Italy (Guerrini et al, 2013), and France (Lannier and Porcher, 2014), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies analysing the performance of the English and Welsh water sector have focused on the 10 WaSCs (Ashton, 2000;Saal & Parker, 2000, 2001Erbetta & Cave, 2007;Saal et al, 2007). The exceptions are Bottasso & Conti (2003), Saal & Parker (2006), Le Lannier (2011), andPortela et al (2011) who assessed the water supply service of both WoCs and WaSCs, and Bottasso & Conti (2009a, 2009b who evaluated the WoCs.…”
Section: Sample and Data Descriptionmentioning
confidence: 99%
“…The importance of assessing the efficiency of the water industry is specially marked in England and Wales where it has come to be an important part of the process of determining the price of the water for urban uses (Cubbin, 2005). In this context, some empirical applications have mainly focused on analysing the impact of the privatization and regulation in productivity (or cost), price performance and/or profitability growth of the water industry (see, for instance, Ashton, 2000;Saal & Parker, 2000, 2001Thanassoulis, 2000;Bottasso & Conti, 2003, 2009a, 2009bErbetta & Cave, 2007;Saal et al, 2007;Maziotis et al, 2009Maziotis et al, , 2012Portela et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Renzetti and Dupont (2009) In a study in which the variable cost function on a group of English and Welsh water and sewerage companies, Bottasso and Conti (2009) evaluated the existence of a ratchet effect in cost cutting efforts related to a price cap regulatory regime. The authors found that cost cutting efforts increase during the early stages of a regulatory cycle and then weakens as price reviews approach.…”
Section: Economic Policiesmentioning
confidence: 99%